The transmission dynamics of groups A and B human respiratory syncytial virus (hRSV) in England & Wales and Finland: seasonality and cross-protection - White, L; Waris, M; Cane, P; Nokes, D; Medley, G (Cambridge University Press, 2005)
Human respiratory syncytial virus (hRSV) transmission dynamics are inherently cyclical, and the observed genetic diversity (between groups A and B) also appears to have a repeating pattern. A key unknown is the extent to which genetic variants interact immunologically, and thus impact on epidemiology. We developed a novel mathematical model for hRSV transmission including seasonal forcing of incidence and temporary intra- and inter-group partial immunity. Simultaneous model fits to data from two locations (England & Wales, UK, and Turku, Finland) successfully reproduced the contrasting infection dynamics and group A/B dominance patterns. Parameter estimates are consistent with direct estimates. Differences in the magnitude and seasonal variation in contact rate between the two populations alone could account for the variation in dynamics between these populations. The A/B group dominance patterns are explained by reductions in susceptibility to and infectiousness of secondary homologous and heterologous infections. The consequences of the observed dynamic complexity are discussed.